2019
DOI: 10.1016/j.htct.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Standardization and quality assessment for clinical grade mesenchymal stem cells from human adipose tissue

Abstract: BackgroundMesenchymal stem cells have immense potential in stem cell-based therapies, however there is a pre-requisite to develop a curative cell dose. Adipose tissue-derived mesenchymal stem cells are promising mainly due to their potential abundance, immunomodulatory effect and remarkable differentiation potential. Nevertheless, senescence may develop during their in vitro expansion due to the incidence of genetic instability. Hence, it is important to attain an ideal balance between mesenchymal stem cell gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…Some studies showed different cell line stabilities in cell phenotype and functional characteristics from P10 up to P30, regarding (54,55) and genomic stability from P5 to P13 (52,53,56). We used cells in a lower passage based on a previous literature that described genomic stability in lower passages and the use of all cells in a similar passage for experimental homogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed different cell line stabilities in cell phenotype and functional characteristics from P10 up to P30, regarding (54,55) and genomic stability from P5 to P13 (52,53,56). We used cells in a lower passage based on a previous literature that described genomic stability in lower passages and the use of all cells in a similar passage for experimental homogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…The number of stem/progenitor cells that can be obtained for use in BTE construct preparation is often limited by the amount of donor material that can be harvested, usually from bone marrow or adipose tissue. While possible, in vitro expansion of donor cells, to reach adequate numbers for therapeutic doses, is not an optimal solution, as it is time consuming and can negatively impact stem cell "quality" [35]. Although EStim has mainly been shown to increase the rate of cell proliferation, contrary findings exist, that show EStim can also decrease, or have no effect on cell proliferation (for general review refer to [36]).…”
Section: Cell Proliferation and Apoptosismentioning
confidence: 99%
“…It is vital to obtain primary cells or cultured cells with fewer passages owing to the dynamic phenotype of ASCs in vitro. Although the selection of optimal passages has also been studied [87,88], the researchers did not report a consistent conclusion. Future studies need to investigate how to isolate, purify, and characterize ASCs in vitro.…”
Section: Application Of Ascs and Future Perspectivesmentioning
confidence: 99%
“…CD34) decreased [11]. The genetic integrity was preserved with minimal alteration up to five passages [87]. It is vital to obtain primary cells or cultured cells with fewer passages owing to the dynamic phenotype of ASCs in vitro.…”
Section: Application Of Ascs and Future Perspectivesmentioning
confidence: 99%